(untitled) - Hiebert, Murray (New York, 1996)
Tells us about condition and policy of Vietnam's economic after the war
Keywords: Vietnam,Việt Nam,Việt Nam; Economic condition,Vietnam,Điều kiện kinh tế,Chính sách kinh tế; Economic policy